Support for Programmatic CDM Development for the National Program for Municipal Solid Waste in Morocco - Lahbabi, Abdelmourhit (World Bank, Washington, DC, 2013)
Carbon Finance Assist (CF-Assist) is a capacity building and technical assistance program established by the World Bank to help develop national capacities of developing countries on carbon finance and clean development mechanism (CDM) activities. The objective of the mission is to develop CDM Program of Activities (PoA), based on a programmatic approach for CDM Project Activities (CPA) in solid waste sector in Morocco. More specifically the assignment consists of the assessment and validation of the feasibility of a nationwide CDM PoA for the solid waste in Morocco and the development of a Program Idea Note (PIN) summarizing the results of the program assessment. Based on the information collected during the mission first phase, an assessment model of the biogas potential was developed for each targeted landfill. The PoA expected emissions reductions were then evaluated for two possible scenarios: an optimistic scenario assuming that all the eligible landfills will develop CDM under the program for both the biogas capture and electricity generation options and a more conservative scenario assuming gas flaring option only in most promising landfills.